Satellite Observations of Strong Plasma Wave Emissions With Frequency Shifts Induced by an Engine Burn From the Cygnus Spacecraft. Issue 2 (23rd February 2021) - Bernhardt, Paul A.; Griffin, Michael K.; Bougas, William C.; Howarth, Andrew D.; James, H. Gordon; Siefring, Carl L.; Briczinski, Stanley J.
Abstract: A new discovery was made using the radio receiver instrument on the Canadian enhanced polar outflow probe (e‐POP) showing that strong plasma wave emissions (SPWE) are seen near 17 kHz and 300 Hz. The frequency of these emissions are affected by small injections of neutral gas from the Cygnus spacecraft. The technique of using a 150 g/s thruster to change frequencies and intensities of plasma waves has provided evidence that a finite k z lower hybrid mode may the source of the SPWE waves. SPWE observations in space are a sensitive diagnostic tool to measure both natural and manmade changes in the earth's ion composition. Key Points: Excitation of strong plasma wave emission (SPWE) in the ionosphere provide sensitive indications of changes in plasma composition VLF SPWEs may be lower hybrid waves excited by the motion of large spacecraft booms moving across magnetic fields in the earth's plasma Firing a 150 g/s rocket engine for 30 s at a range of 50 km from enhanced polar outflow probe electric field sensor yielded large changes in the SPWE spectra